ANALISIS KEBUTUHAN PELATIHAN PEGAWAI TATA USAHA BAGIAN ADMINISTRASI SMK NEGERI 1 CIBINONG - Andayani, Asti; Rustianingsih, Diani (Economicus, 2020)
SMK NEGERI 1 Cibinong is an educational institution, whose function is to help someone to have the expertise to live in society, and to develop their and the community's potential. This research was conducted at SMK Negeri 1 Cibinong. The method used for data analysis is the Training Need Assessment Tool (TNA-T), to find out a gap between the Occupational Ability (KKJ) and Personal Ability (KKP). Respondents numbered 12 people. KKP and KKJ measurement indicators are the skills and expertise of employees in carrying out their work and the individual potential of each employee.The results of this study indicate that the analysis of training needs is very important to see the extent of the capabilities of employees, using the Training Need Assessment Tool (TNA-T). From the results of the questionnaire that has been distributed to employees and then processed using the Microsoft Office Excel 2010 program, it is found that there is a gap between Occupational Job Capability (KKJ) and Personal Work Ability (KKP). Services, Staffing Planning, Receiving and using budget funds, Managing outgoing mail, Inventory, Managing records, and Managing student activities are urgently needed for training.